Analysis of centralized public procurement of medicines in Ukraine with the involvement of international organizations - V. S. Zlahoda; T. A. Germanyuk; L. O. Bobrytska; O. S. Shpychak; V. M. Nazarkina (The State Expert Center of the Ministry of Health of Ukraine, 2022)
The Ministry of Health of Ukraine carries out centralized procurement of drugs in 40 priority areas with the involvement of international organizations «UNDP», «UNICEF» and «Crown Agents» and regional procurement from local budgets and the reimbursement program «Affordable medicines».This procedure increases drugs accessibility, medical care quality and pharmaceutical provision of the population. The aim of the work is analyze the current state and effectiveness of centralized drugs procurement through the Ministry of Health in Ukraine. The object of research is the data of official statistics, regulations, scientific publications, public module of analytics programm VI ProZorro. The research was conducted using methods of content-analysis, systematization and generalization. Analysis of the dynamics of procurement of drugs involving the Ministry of Health in 2018‒2020 revealed a trend of increasing the amount of budget funds provided for the purchase of drugs in 2020 by 60% compared in 2018. In 2020, 14 procurement programs were transferred State Enterprise «Medical Procurement of Ukraine», they were performed using the electronic system «ProZorro» with the participation of a large number of international drug companies. A comparative analysis of drugs prices purchased in 2017‒2020 in the fields of «Children's Oncology» and «Adult Oncology». The decrease in drugs prices is due to competition and direct participation of drug manufacturers in tenders; entering the market of new generics, introduction of transparent mechanisms of electronic auctions, etc. Some drugs in 2020 were purchased in higher prices due to lower order volumes; quarantine restrictions, including import restrictions; rising prices for substances for the manufacture of drugs. Centralized procurement of drugs and medical commodities in Ukraine is carried out by the Ministry of Health with the involvement of international organizations «UNDP», «UNICEF» and «Crown Agents». These are temporary measures implemented in 2015 in connection with the reform of the public procurement system, aimed at reducing corruption risks and improving the pharmaceutical supply of the population. Such purchases are made in 40 fields, the total amount is about UAH 6 billion per year. Involvement of international organizations in centralized public procurement of medicines in Ukraine and implementation of a reimbursement program for medicines, including for the treatment of cardiovascular diseases reduces the price and ensures the availability of drugs for the population.